Evidence for an aseismic gap between the Mw6.8 Puturge (Elazig) and 7.8 Pazarcik (Kahramanmaras,) earthquakes in the east Anatolian fault system, southeast Turkiye - Akgun, Elif; Topal, Savas; Softa, Mustafa; Nas, Murat; Gurgoze, Serkan; Sozbilir, Hasan; Yuksel, Mehmet (Pergamon-Elsevier Science Ltd, 2025)
This study examines the unruptured portion of the Puturge segment, the least-studied section of the East Anatolian Fault System (EAFS) in southeast Turkiye, focusing on the S,iro Valley to comprehensively understand the observed distribution in deformation. Despite the February 6, 2023 doublet earthquakes, the Puturge segment near the S,iro Valley remained relatively stable, though significant stress accumulation was detected at both ends. Fieldwork and subsequent morphometric and structural analyses confirmed notable tectonic activity in the area. Geomorphic indices were applied to assess tectonic activity, yielding an average index of relative tectonic activity (Iat) for all drainage basins, highlighting varying tectonic intensity levels across the S,iro Valley. Mountain front sinuosity (Smf) analysis indicated different uplift rates and tectonic forces along distinct fault segments. Additionally, Hypsometric Integral-Hypsometric Curve (HI-HC) index analysis pointed to rapid uplift processes, particularly in the eastern part of the fault-controlled basin, signaling active tectonic uplift and geomorphic rejuvenation. Normalized steepness index (ksn) and Chi (chi) values highlighted variations in erosion rate, providing insight into regional uplift patterns and knickpoint distributions. These findings align with the dominant transtensional tectonic regime in the area, as inferred from slip data inversions along the S,iro Valley. The region's fault geometry, oblique movement, and block rotations firmly support this interpretation. Comparisons of slip rates and ground deformation models revealed notable variations in fault behavior, suggesting ongoing energy accumulation, possibly linked to aseismic creep. The complex fault system behavior was underscored by the 2020 Sivrice earthquake and the 2023 doublet, which highlights the critical role of the Puturge segment in the dynamic evolution of the EAFS.
Keywords: Puturge segment; East Anatolian fault system; Morphometric index; Kinematic analysis; Kahramanmaras , earthquakes